Personality and COMT gene: molecular-genetic and epigenetic associations with NEO-PI-R personality domains and facets in monozygotic twins - Mitrović, Dušanka; Smederevac, Snežana; Delgado-Cruzata, Lissette; Sadiković, Selka; Pajić, Dejan; Prinz, Mechthild; Budimlija, Zoran; Oljača, Milan; Kušić-Tišma, Jelena; Vučinić, Nataša; Milutinović, Aleksandra (Frontiers in Genetics, 2024)
Background This study investigates the relationship between MB-COMT DNA methylation (DNAm) and the personality traits outlined in the NEO-PI-R model through an epigenetic study of monozygotic twins. DNAm, a critical epigenetic mechanism, regulates gene expression and has been linked to various biological processes and disorders. By leveraging the genetic similarities of monozygotic twins, this research explores how epigenetic variations influenced by environmental factors correlate with personality differences. Methods The study utilized the Five-Factor Model (FFM) to categorize personality traits into five domains: Neuroticism, Extraversion, Conscientiousness, Agreeableness, and Openness to Experience. Each domain comprises six facets, providing a granular view of personality. The research centered on the catechol-O-methyltransferase (COMT) gene, focusing on its role in dopamine metabolism, which is hypothesized to influence personality traits through the dopaminergic system. DNAm status in the MB-COMT promoter region was examined to determine its association with personality facets. Results Preliminary findings suggest a complex interaction between MB-COMT DNAm patterns and personality traits. Specific methylation patterns at different CpG sites were linked to varying expressions of traits such as impulsivity and aggression, highlighting the nuanced impact of epigenetics on personality. Conclusion This study underscores the potential of integrating genetic, epigenetic, and environmental data to enhance our understanding of personality formation. The results contribute to a broader understanding of how genetic predispositions shaped by environmental factors manifest in complex trait differences, paving the way for future research in genetic psychiatry and personalized medicine.